Predictors of knowledge, attitude and practice among seropositive leptospirosis cattle farmers in northeastern Malaysia - Daud, Aziah; Mohd Basri, Ijlal Syamim; Ahmad, Elyas; Wan Mohammad, Wan Mohd Zahiruddin; Ismail, Nabilah; Amran, Fairuz
Leptospirosis is a neglected re-emerging disease, with Kelantan being the leading state in Malaysia for its annual incidence. Among agricultural workers, cattle farmers significantly contribute to the high incidence in Kelantan. In 2018, a high seroprevalence of leptospirosis (72.5%) was reported among these farmers. Despite various studies on leptospirosis in Kelantan, none have focused on cattle farmers. This study aims to assess knowledge, attitudes, and practices (KAP) levels and identify associated factors among seropositive leptospirosis cattle farmers in Kelantan. Methodology: This cross- sectional study utilized an interviewer-guided validated questionnaire to collect data from all seropositive leptospirosis cattle farmers in Kelantan. A Likert scale was used to score KAP, with total scores converted to percentages. Descriptive analysis was performed using IBM SPSS version 24.0. Result: Most respondents (64.4%) demonstrated good knowledge of leptospirosis, yet only 38.4% had a satisfactory attitude, and a mere 16.4% practised satisfactory preventive measures. Not eating or drinking at the workplace was associated with good knowledge, satisfactory attitudes, and practices. Wearing rubber boots and experiencing rat infestation at the workplace were linked to good knowledge. Living more than 200 meters from a river correlated with satisfactory attitudes while increasing age was associated with better practices. Additionally, wearing rubber gloves was linked to satisfactory practices. Conclusion: Despite their good knowledge, respondents exhibited unsatisfactory attitudes and practices toward leptospirosis prevention. Future efforts should focus on improving attitudes and practices to enhance preventive measures against leptospirosis.